Clays and Clay Minerals, Vol. 56, No. 1, 39–48, 2008. - Lantenois, Se´bastien; Muller, Fabrice; Be´ny, Jean-michel; Mahiaoui, Jamel; Champallier, Re´mi (The Clay Minerals Society, 2008)
Low-charge beidellites were synthesized by a hydrothermal treatment applied to an amorphous gel phase in basic solution. The hydrothermal conditions for the syntheses were chosen from the stability field of beidellite previously investigated in the literature. The synthetic samples were characterized chemically and structurally using X-ray diffraction, infrared spectroscopy, cation exchange capacity measurement, and chemical and thermal analyses. We compared the synthetic sample with a natural beidellite sample (SbId) from Idaho, USA, looking at chemical composition and particle size. The main difference is the octahedral site occupancy (cis- or trans-vacant layer structure). The natural SbId sample has trans-vacant layers and the synthetic sample has a preferentially cis-vacant character. This character can be modulated, using specific synthesis conditions. The cis- or trans-vacant layer structure of various synthetic beidellites was investigated at low temperature (<350ºC) and pressure (<25 MPa). Depending on the pressure and/or synthesis temperature, the proportion of cis-vacant layers ranges from 20 to 100% and increases with the layer-charge deficit.
Hydrothermal Synthesis Of Beidellites: Characterization And Study Of The Cis- And Trans-vacant Character
Clays and Clay Minerals, Vol. 56, No. 1, 39–48, 2008. Hydrothermal Synthesis Of Beidellites: Characterization And Study Of The Cis- And Trans-vacant Character. Se´bastien Lantenois; Fabrice Muller; Jean-michel Be´ny; Jamel Mahiaoui; Re´mi Champallier. DOI: 10.1346/CCMN.2008.0560104. Copyright © 2008, The Clay Minerals Society
Keywords: Periodicals; Geology; Beidellite; Chemical Analyses; Cis-vacant Layer; FTIR Spectroscopy; Hydrothermal Syntheses; Smectite; TGA; Trans-vacant Layer; XRD